„Parašykite, kad badas buvo dirbtinis“: asmeniniai šaltiniai apie 1932–1933 m. Holodomorą Ukrainoje - Boriak, Tetiana (Genocidas ir rezistencija, 2023)
The author proposes classification of the Holodomor source base for a better understanding of the context of historical research on the issue. The author divides the sources into two large segments: official documentation deposited in archival institutions and sources of personal origin. The first segment includes five groups. Analysing the state of the sources of this segment, the author focuses on the gaps due to “archivocide” as the deliberate destruction by the Soviet authorities of traces of the famine in official documentation and the specifics of documenting administrative decisions of that period. That is why sources of personal origin constitute a significant segment of the Holodomor source base and should be more widely used in research. Here the author managed to identify six groups of unequal size. The article presents thematic blocks of sources of personal origin and gives examples of various types of such sources. A conclusion is made about the continuity of the narrative about the famine in the sources of personal origin and in the individual memory of Ukrainians. Here it is emphasized that the sources about the famine, which are diverse in types and authorship, did not appear out of nowhere in the post-war period or in the 1980s, but began to appear as early as 1932.
Keywords: Holodomor; source base; sources of personal origin; oral history; history of Soviet totalitarianism